Characteristics of microalbuminuria among patients with type 2 diabetes mellitus treated at Saigon general hospital - Hao, Phan Thai; Huy, Mai Duc; Thanh, Tran Thi Ngoc; Quan, Phung Nguyen (Edelweiss Applied Science and Technology, 2026)
Early detection of microalbuminuria in patients with type 2 diabetes mellitus is essential for preventing diabetic kidney disease. Microalbuminuria testing is widely recommended from the time of diagnosis to monitor complications. To describe the characteristics of microalbuminuria in T2DM patients treated at Saigon General Hospital in 2025. Materials and Methods: A prospective cross-sectional study was conducted on 89 T2DM patients at the Department of General Internal Medicine from April to September 2025. The prevalence of microalbuminuria (MAU ≥30 mg/L) was 23.6%. Mean MAU levels were 71.5±92.6 mg/L in males and 64.7±89.8 mg/L in females. Patients with positive MAU had higher HbA1c (8.0±1.4%), serum creatinine (89.8±22.1 µmol/L), and BMI (25.3±3.2 kg/m²), indicating an association between poor glycemic control, increased body weight, and early renal impairment. Hypertension was present in 66.7% of patients with MAU. Microalbuminuria is relatively common in T2DM patients and is associated with modifiable risk factors. Routine screening is important for early detection and timely intervention to prevent progression to diabetic nephropathy.